Creative destruction and productivity growth in an emerging economy : evidence from Slovenian manufacturing - Jan De Loecker; Jozef Konings (Institute for the Study of Labor (IZA), 2003)
In most transition countries the aggregate level evidence suggests that most industries are just destroying jobs, due to the legacy of communism where over-manning levels of employment were the norm. This paper sheds light on whether the transition process in Slovenian manufacturing has been one of just destruction or in contrast one of creative destruction. To this end we start by documenting gross job flows for the Slovenian manufacturing sector between 1994 and 2000. In contrast to slowly reforming transition economies where the transition process in manufacturing is characterized by little job creation and high job destruction, we find for Slovenian manufacturing a process of both substantial job creation and destruction. This indicates that restructuring in Slovenia involves a substantial reallocation process. We find higher job reallocation in private and small firms where the contribution of entry and exit to the job reallocation process is higher. We further use the Olley-Pakes methodology to estimate total factor productivity (TFP) and show that TFP has increased in most sectors. We find that this is mainly driven by existing firms becoming more efficient and by the net entry process, i.e. more efficient firms enter the industry.
Keywords: P20; D21; L60; 330; creative destruction; total factor productivity; reallocation; Produktivität; Arbeitsmarkt; Personalabbau; Arbeitsmobilität; Personalbeschaffung; Industrieller Strukturwandel; Übergangswirtschaft; Slowenien